Implementation of IV Push Antibiotics for Outpatients During a National Fluid Shortage Following Hurricane Maria. (21st March 2022) - Yagnik, Kruti J; Brown, L Steven; Saad, Hala A; Alvarez, Kristin; Mang, Norman; Bird, Cylaina E; Cerise, Fred; Bhavan, Kavita P
Abstract: Background: Prior to the introduction of intravenous (IV) drip infusion, most IV drugs were delivered in a syringe bolus push. However, intravenous drip infusions subsequently became the standard of care. Puerto Rico is the largest supplier of IV fluid bags and in the aftermath of Hurricane Maria, there was a nationwide fluid bag shortage. This shortage required stewardship measures to maintain the operation of the self-administered outpatient parenteral antimicrobial therapy (OPAT) program at Parkland Health. Methods: Parkland pharmacists evaluated all self-administered antimicrobials for viability of administration as an IV syringe bolus push (IVP) instead of an IV-drip infusion. Medications deemed appropriate were transitioned to IVP. The hospital EMR was used to identify patients discharged to the OPAT clinic using all methods of parenteral drug delivery. Data was collected for patient demographics, patient satisfaction, and clinical outcomes. Finally cost of care was calculated for IVP and IV drip administration. Results: One-hundred and thirteen self-administered IVP and 102 self-administered IV drip treatment courses were identified during the study period. Individuals using IVP had a statistically significant decrease in hospital length of stay. Patient satisfaction was greater with IVP and IVP saved 504 liters of normal saline resulting in a savings of $43, 652 over 6 months. The 30-day readmission rate and mortality were similar. Conclusion: The abrupt IV fluid shortage following a natural disaster led to implementation of a high value care model that improved efficiency, reduced costs, and did not affect safety or efficacy.